2018
DOI: 10.1007/s00425-018-2876-z
|View full text |Cite
|
Sign up to set email alerts
|

Generation of advanced fire blight-resistant apple (Malus × domestica) selections of the fifth generation within 7 years of applying the early flowering approach

Abstract: Main conclusionThe approach presented here can be applied to reduce the time needed to introduce traits from wild apples into null segregant advanced selections by one-fourth.Interesting traits like resistances to pathogens are often found within the wild apple gene pool. However, the long juvenile phase of apple seedlings hampers the rapid introduction of these traits into new cultivars. The rapid crop cycle breeding approach used in this paper is based on the overexpression of the birch (Betula pendula) MADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Fast-track breeding via transgenesis 297,298 or induced through a plant virus vector 299 might enable full realization of GP potential in apple. While SSRs were used to select for a favorable QTL allele and against unfavorable genetic background over five generations in seven years 300 , GP can be used to identify elite progeny across a range of traits. Implementation of GP for apple improvement might require modification of breeding programs and stochastic simulation can be used to evaluate benefits of different strategies 290 .…”
Section: Genomic Prediction: Genome-wide Performance Forecasting Blamentioning
confidence: 99%
“…Fast-track breeding via transgenesis 297,298 or induced through a plant virus vector 299 might enable full realization of GP potential in apple. While SSRs were used to select for a favorable QTL allele and against unfavorable genetic background over five generations in seven years 300 , GP can be used to identify elite progeny across a range of traits. Implementation of GP for apple improvement might require modification of breeding programs and stochastic simulation can be used to evaluate benefits of different strategies 290 .…”
Section: Genomic Prediction: Genome-wide Performance Forecasting Blamentioning
confidence: 99%
“…Early flowering has been demonstrated in apple through the overexpression of beech MADS4 and Arabidopsis FT gene (Flachowsky et al, 2007 ; Yamagishi et al, 2011 ). This technology has been used to rapidly breed fire blight resistance into apple within 7 years (Schlathölter et al, 2018 ). A similar result has been obtained using antisense-based silencing of MdTFL1 expression (Kotoda et al, 2006 ).…”
Section: Potential Applications Of Gene Editing In New Zealandmentioning
confidence: 99%
“…linkage between the gene of interest and undesirable genes that are inherited together from the donor parent), so repeated PBC with elite parents is applied to minimise the non-desirable genomic content of the donor parent in selected seedlings. In addition to the foreground MAS for major genes, a marker-based background selection (which involves selection of only those resistant seedlings that have inherited the least proportion of donor genome) can also be incorporated in a PBC breeding strategy [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…growth chamber) methods have been suggested to reduce the juvenility period 8,10 . Alternatively, a transgenic early flowering approach for the introgression of fire-blight resistance from the wild apple 'Evereste', showed that five breeding cycles could be completed within seven years 9 . However, transgenic plants are still regulated in many countries, so this strategy cannot be used for commercial cultivar breeding at the moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation